The major stratospheric final warming in 2016: dispersal of vortex air and termination of Arctic chemical ozone loss - G. L. Manney; G. L. Manney; Z. D. Lawrence (Atmospheric Chemistry and Physics, 2016)
The 2015/16 Northern Hemisphere winter stratosphere appeared to have the greatest potential yet seen for record Arctic ozone loss. Temperatures in the Arctic lower stratosphere were at record lows from December 2015 through early February 2016, with an unprecedented period of temperatures below ice polar stratospheric cloud thresholds. Trace gas measurements from the Aura Microwave Limb Sounder (MLS) show that exceptional denitrification and dehydration, as well as extensive chlorine activation, occurred throughout the polar vortex. Ozone decreases in 2015/16 began earlier and proceeded more rapidly than those in 2010/11, a winter that saw unprecedented Arctic ozone loss. However, on 5–6 March 2016 a major final sudden stratospheric warming ("major final warming", MFW) began. By mid-March, the mid-stratospheric vortex split after being displaced far off the pole. The resulting offspring vortices decayed rapidly preceding the full breakdown of the vortex by early April. In the lower stratosphere, the period of temperatures low enough for chlorine activation ended nearly a month earlier than that in 2011 because of the MFW. Ozone loss rates were thus kept in check because there was less sunlight during the cold period. Although the winter mean volume of air in which chemical ozone loss could occur was as large as that in 2010/11, observed ozone values did not drop to the persistently low values reached in 2011. We use MLS trace gas measurements, as well as mixing and polar vortex diagnostics based on meteorological fields, to show how the timing and intensity of the MFW and its impact on transport and mixing halted chemical ozone loss. Our detailed characterization of the polar vortex breakdown includes investigations of individual offspring vortices and the origins and fate of air within them. Comparisons of mixing diagnostics with lower-stratospheric N2O and middle-stratospheric CO from MLS (long-lived tracers) show rapid vortex erosion and extensive mixing during and immediately after the split in mid-March; however, air in the resulting offspring vortices remained isolated until they disappeared. Although the offspring vortices in the lower stratosphere survived longer than those in the middle stratosphere, the rapid temperature increase and dispersal of chemically processed air caused active chlorine to quickly disappear. Furthermore, ozone-depleted air from the lower-stratospheric vortex core was rapidly mixed with ozone rich air from the vortex edge and midlatitudes during the split. The impact of the 2016 MFW on polar processing was the latest in a series of unexpected events that highlight the diversity of potential consequences of sudden warming events for Arctic ozone loss.